New Taipei City Smart Pavement Management Center and Road Maintenance Analysis - Pin-You Song; Jyh-Dong Lin; Min-Che Ho; Chia-Chi Zou (Applied Sciences)
The integration of the Smart Pavement Management Center aims to improve the efficiency and quality of road maintenance in New Taipei City. This paper explores the application of the I-ROAD Reporting System and analyzes its effectiveness in providing real-time road condition updates and alerts, which assist road authorities in making timely decisions. Additionally, the study establishes a comprehensive road maintenance lifecycle model, encompassing road construction, maintenance, repair, and milling. This model systematically manages road resources to reduce maintenance costs and extend the service life of roads. Through the optimization of inspection methods and the evaluation and selection of construction techniques, the most cost-effective solutions were identified to improve the efficiency and quality of maintenance work. Lastly, the paper discusses how to optimize the budget for road maintenance within financial constraints by applying scientific budget allocation and management strategies. This ensures the efficient use of funds and that road conditions are maintained at an optimal level. This study explores the use of a road management system for the analysis and optimization of future road maintenance projects. Within a limited budget, it aims to achieve optimal allocation and management of maintenance funds through scientific financial planning, ensuring efficient use of resources to maintain road conditions at an optimal level.